2012
DOI: 10.1186/1471-2180-12-143
|View full text |Cite
|
Sign up to set email alerts
|

Roles of iron acquisition systems in virulence of extraintestinal pathogenic Escherichia coli: salmochelin and aerobactin contribute more to virulence than heme in a chicken infection model

Abstract: BackgroundAvian pathogenic Escherichia coli (APEC) and uropathogenic E. coli (UPEC) are the two main subsets of extraintestinal pathogenic E. coli (ExPEC). Both types have multiple iron acquisition systems, including heme and siderophores. Although iron transport systems involved in the pathogenesis of APEC or UPEC have been documented individually in corresponding animal models, the contribution of these systems during simultaneous APEC and UPEC infection is not well described. To determine the contribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
86
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 52 publications
2
86
0
1
Order By: Relevance
“…However, the larger haloes around some colonies, particularly the ExPEC isolates, are consistent with the known ability of ExPEC to produce other siderophores, such as aerobactin, salmochelin, and yersiniabactin (48,49), and this is supported here by the positive correlation between CAS agar halo diameter and the siderophore receptor genes iutA and iroN. The role of siderophores in the virulence of ExPEC is well established, as exemplified by a recent study that showed the importance of aerobactin and salmochelin in the virulence of both APEC and UPEC in a chicken model (50). Future studies should assess whether these ExPEC-associated iron uptake systems also promote bacterial persistence on poultry products, especially meat.…”
Section: Discussionsupporting
confidence: 66%
“…However, the larger haloes around some colonies, particularly the ExPEC isolates, are consistent with the known ability of ExPEC to produce other siderophores, such as aerobactin, salmochelin, and yersiniabactin (48,49), and this is supported here by the positive correlation between CAS agar halo diameter and the siderophore receptor genes iutA and iroN. The role of siderophores in the virulence of ExPEC is well established, as exemplified by a recent study that showed the importance of aerobactin and salmochelin in the virulence of both APEC and UPEC in a chicken model (50). Future studies should assess whether these ExPEC-associated iron uptake systems also promote bacterial persistence on poultry products, especially meat.…”
Section: Discussionsupporting
confidence: 66%
“…The role of aerobactin in the virulence of ExPEC is well documented for UPEC and avian-pathogenic E. coli (APEC) strains. Indeed, aerobactin is involved in the virulence of APEC strains 7122 and E058, as different iuc mutants presented decreased colonization of several organs during systemic infection of poultry (45,46,50,51). An iucD mutant of the UPEC strain U17 was also attenuated in a chicken model of colibacillosis (45).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aerobactin is involved in the virulence of APEC strains 7122 and E058, as different iuc mutants presented decreased colonization of several organs during systemic infection of poultry (45,46,50,51). An iucD mutant of the UPEC strain U17 was also attenuated in a chicken model of colibacillosis (45). In a murine model of infection, a mutant of the UPEC strain CFT073 deficient in enterobactin and aerobactin production was also attenuated in the colonization of bladders and kidneys (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…coli has developed complex mechanisms to survive and proliferate inside the host (47)(48)(49)(50). APEC must escape a multitude of host defense mechanisms in order to cause septicemia.…”
Section: Discussionmentioning
confidence: 99%